Pedagogical technologies in the formation of intercultural competence in history lessons (MMIT Proceedings, 2025)
This article analyzes modern pedagogical technologies in the formation of intercultural competence in history lessons. Interactive approaches, multimedia tools, and project-based learning are introduced into the lesson methodology, and the methodology for their effective use is considered. The article assesses the didactic effectiveness of these pedagogical technologies based on scientific literature